5-Hydroxymethylfurfural production from dehydration of fructose catalyzed by Aquivion@silica solid acid. (15th February 2018) - Dou, Youwei; Zhou, Shuai; Oldani, Claudio; Fang, Wenhao; Cao, Qiue
Graphical abstract: Highlights: Mesoporous silica obtained from TEOS using Aquivion PFSA as acidic and template agent. Highly accessible SO3 H sites of Aquivion PFSA attached firmly to porous silica. 85% yield of HMF obtained from fructose at 90 °C in the presence of DMSO. Aquivion@silica solid acid behaving as stable and reusable catalyst. Abstract: 5-Hydroxymethylfurfural (HMF) production from catalytic dehydration of fructose was studied over mesoporous silica heterogenized perfluorosulfonic acid resin (Aquivion@silica) catalyst. Amphiphilic Aquivion PFSA was used as both acidic and template agent for the sol–gel synthesis of amorphous mesoporous silica which was found very appropriate to effectively immobilize Aquivion resin by using an impregnation method. Various characterizations including elemental analysis, acid-base titration, XRD, FTIR, Raman, N2 adsorption–desorption, SEM and TEM revealed that Aquivion@silica catalyst presented large surface area, sufficient porosity and afforded highly accessible sulfonic acid groups. Efficient and productive HMF production from the dehydration of fructose was achieved in the polar dimethyl sulfoxide (DMSO) solvent at low temperature of 90 °C, i.e. 85% yield of HMF and 43 molHMF molH+ productivity of HMF. The influence of reaction time, reaction temperature, Aquivion loading, catalyst dosage and solvent on the dehydration process was systematically investigated. The catalyst could be regenerated through a simple ion-exchange method and a stable HMF yield was maintained after being used four times.